2012
DOI: 10.1002/jbm.b.32798
|View full text |Cite
|
Sign up to set email alerts
|

In vitro analysis of the cytotoxic and anti‐inflammatory effects of antioxidant compounds used as additives in ultra high‐molecular weight polyethylene in total joint replacement components

Abstract: Ultra high-molecular weight polyethylene (UHMWPE) remains the most commonly used material in modern joint replacement prostheses. However, UHMWPE wear particles, formed as the bearing articulates, are one of the main factors leading to joint replacement failure via the induction of osteolysis and subsequent aseptic loosening. Previous studies have shown that the addition of antioxidants such as vitamin E to UHMWPE can improve wear resistance of the polymer and reduce oxidative fatigue. However, little is known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…1,9,20 In particular, it has been demonstrated that oxidative degradation of UHMWPE gamma-sterilized in air increased its wear while decreasing mechanical strength, constituting the main cause of the dramatic implant failures occurred in the last years. [21][22][23] As a consequence, many efforts have been made to improve UHMWPE quality and performance, for example through the reduction or elimination of the oxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,9,20 In particular, it has been demonstrated that oxidative degradation of UHMWPE gamma-sterilized in air increased its wear while decreasing mechanical strength, constituting the main cause of the dramatic implant failures occurred in the last years. [21][22][23] As a consequence, many efforts have been made to improve UHMWPE quality and performance, for example through the reduction or elimination of the oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a significant decreased bacterial adhesion was registered for both bacteria on VE-PE, in comparison with that observed on PE, within 48h of observation ( Figure 3 A and B), underlying the role of VE, probably related to its well established antioxidant properties. 9,20 The mechanism by which VE may affect the bacterial adherence to UHMWPE it is currently unknown, even if potential effects of VE on infection are currently investigated. 25 The CA measurements showed no significant variations in hydrophilicity between PE and VE-PE suggesting that other, concurrent factors must be involved in the different bacterial adhesion.…”
Section: S Epidermidismentioning
confidence: 99%
“…20,24 Moreover, it has been shown that VE when added to UHMWPE does not have any cytotoxic effects and acts as an effective anti-inflammatory. 9 In this study we quantified the adhesion of well-characterized biofilm producing collection strains of S. aureus and E. coli, as pathogens mostly associated with periprosthetic infection, to standard UHMWPE, to VE blended UHMWPE and to oxidized UHMWPE taking into account that for a given material surface, different bacterial species and strains adhere differently since different species and strains have different physicochemical characteristics: 14,15 slime producer S. epidermidis and S. aureus have a comparatively thicker and more rigid peptidoglycan layer respect to a fimbriae producer E. coli, and extensive contact of their external cell-structure with the implant surface may be quite different. S. aureus produces many toxins and tissue damaging exoenzymes, compared to…”
Section: Discussionmentioning
confidence: 99%
“…7 However, it has been demonstrated that oxidation has been the main cause of many dramatic implant failures in the last two decades. 3,[7][8][9] Therefore many efforts have been made to improve the quality and the performance of UHMWPE in vivo, through reducing or eliminating the oxidation. Vitamin E (VE; alpha-tocopherol) was first introduced into conventional UHMWPE in an attempt to decrease the delamination caused by oxidative fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…The phenoxy radicals in HPAO stabilize the free alkyl radicals in the same manner. However, the cyto-compatibility of these compounds still needs to be established 12). The antioxidant anthocyanin is freely available in plants, flowers, and fruits like grapes and berries and is observed to have antioxidant properties four times that of vitamin E. Anthocyanin-doped, ultra-high molecular weight polyethylene (UHMWPE) is already under production.…”
Section: Bearing Surfaces In Research or Clinical Trialsmentioning
confidence: 99%